2004
DOI: 10.4025/actascibiolsci.v26i2.1635
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da maturação gonadal sobre o conteúdo calórico e condição geral de peixes da planície de inundação do alto rio Paraná

Abstract: RESUMO.Com o intuito de investigar a alocação de energia e a correlação entre esta e o fator de condição (K) de peixes da planície de inundação do alto rio Paraná (22º43'S; 53 O 32'W), foram selecionadas as espécies Serrasalmus marginatus (piscívora), Loricariichthys platymetopon (detritívora), Leporinus friderici (onívora-herbívora) e Parauchenipterus galeatus (onívora-insetívora). As coletas foram realizadas em novembro/2002, março e setembro/2003. As amostras de músculos de indivíduos de ambos os sexos p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1
14

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 16 publications
0
8
1
14
Order By: Relevance
“…The same was observed for the females of Schizodon borellii and Pimelodus maculatus (Doria and Andrian, 1997), females of Brycon hilarii, and both sexes of Hypophthalmus edentatus (Monteiro et al, 2007). However, Vismara et al (2004) observed that gonadal maturation had an effect on the allocation of muscle energy of L. platymetopon in the Upper Paraná River floodplain, as opposed to what was observed in the present study. This effect had also been observed for the males of Serrassalmus marginatus, S. maculatus and Brycon hilarii at the Manso reservoir and adjacent area (Santos et al, 2006;Monteiro et al, 2007).…”
Section: Discussioncontrasting
confidence: 57%
“…The same was observed for the females of Schizodon borellii and Pimelodus maculatus (Doria and Andrian, 1997), females of Brycon hilarii, and both sexes of Hypophthalmus edentatus (Monteiro et al, 2007). However, Vismara et al (2004) observed that gonadal maturation had an effect on the allocation of muscle energy of L. platymetopon in the Upper Paraná River floodplain, as opposed to what was observed in the present study. This effect had also been observed for the males of Serrassalmus marginatus, S. maculatus and Brycon hilarii at the Manso reservoir and adjacent area (Santos et al, 2006;Monteiro et al, 2007).…”
Section: Discussioncontrasting
confidence: 57%
“…Estes autores encontraram, ainda, neste mesmo estádio, elevados valores calóricos e justificaram pelo fato de que é no período de preparação das gônadas para a reprodução que ocorrem as mais elevadas concentrações energéticas no organismo, visando suprir a demanda necessária à realização dos eventos reprodutivos. Por outro lado, as menores variabilidades foram encontradas no início e término do período reprodutivo (Figura 3A) Este padrão registrado para as duas espécies analisadas, no presente estudo, não foi constatado por Vismara et al (2004), para Loricariichthys platymetopon e por Santos et al (2006), para Serrasalmus marginatus. Maiores investigações devem ser conduzidas a fim de identificar quais os fatores fisiológicos ou ecológicos responsáveis por estas variações.…”
Section: Brycon Hilarii Brycon Hilarii Brycon Hilarii Brycon Hilariiunclassified
“…Na literatura, não é descrito, para esta espécie, o estádio REP para machos (Benedito-Cecilio e Agostinho, 1991). Portanto, constata-se que, imediatamente após o período de reprodução e início de um novo ciclo, os indivíduos já ingressaram num processo de recuperação e armazenamento de energia, pois grupos ou cistos de espermatogônias e ovogônias organizam-se para reiniciar o processo de maturação gonadal (Vismara et al, 2004).…”
Section: Hypophthalmus Edentatus Hypophthalmus Edentatus Hypophthalmuunclassified
See 1 more Smart Citation
“…Bianchini Junior (2003) affirms that each group responds to the abiotic and biotic factors in a different way, in accordance with adopted survival strategies. In the preparation of energy flow models that explain food webs, energy data from Upper Paraná river floodplain macrophytes had not yet been obtained, considering that studies had only been made with animal groups (Benedito-Cecilio and Morimoto, 2002;Benedito-Cecilio, et al, 2004;Vismara et al, 2004). So, this work had as its aim the analysis of the caloric density of the leaves, stems and roots of aquatic macrophytes collected in the Baía river and in two lagoons of its subsystem.…”
Section: Introductionmentioning
confidence: 99%